Brain 5-HT neurotransmission during paroxetine treatment. - Sargent, P; Williamson, D; Cowen, P (1998)
BACKGROUND: Animal experimental studies suggest that repeated administration of selective serotonin reuptake inhibitors (SSRIs) produces complex adaptive changes in brain serotonin (5-HT) pathways. The effect of these adaptive changes on different aspects of brain 5-HT neurotransmission and their clinical consequences are not well understood. METHOD: We studied the effect of repeated administration of the SSRI, paroxetine (20 mg daily), on the cortisol responses to the 5-HT precursor, 5-hydroxytryptophan (5-HTP), in healthy subjects and depressed patients. RESULTS: In healthy subjects, following one week of paroxetine treatment there was a large increase in the cortisol response to 5-HTP. This increase had all but disappeared following 3 weeks treatment. In contrast, in depressed patients treated with paroxetine for 8 weeks, the cortisol response to 5-HTP was significantly increased. CONCLUSIONS: SSRI treatment in depressed patients produces a persistent increase in the cortisol response to 5-HTP, a probable measure of neurotransmission at central 5-HT2 receptors. Potentiation of 5-HT2 neurotransmission is unlikely to account for the efficacy of SSRIs in major depression but might underlie their actions in obsessive-compulsive disorder and also perhaps certain of their adverse effects, notably sexual dysfunction.